2022
DOI: 10.1186/s12871-021-01550-z
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative and quantitative gastric ultrasound assessment in highly skilled regional anesthesiologists

Abstract: Background Pulmonary aspiration is a major complication in anesthesia, and various studies have shown that gastric sonography can reliably provide valuable information relative to both the qualitative and quantitative aspects of gastric content. This study aimed to determine the accuracy of ultrasound assessment of gastric content compared between two novice anesthesiologist gastric sonographers. Methods This prospective cohort study of two anesthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…The nine articles included four randomized controlled studies [ 4 , 28 – 30 ] and five cohort studies [ 23 – 27 ]. Seven articles used randomization to fluid intake (clarified liquids/milk), solid food, or fasting in subgroups as the gold standard for assessing the accuracy of gastric ultrasound, and six of these studies were conducted in healthy volunteers [ 4 , 23 , 25 , 28 – 30 ], whereas the study by Arzola et al was conducted in women with late-term pregnancies [ 24 ]. Segura-Grau et al studied patients requiring upper gastrointestinal endoscopy, using endoscopic findings of gastric contents as the gold standard [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The nine articles included four randomized controlled studies [ 4 , 28 – 30 ] and five cohort studies [ 23 – 27 ]. Seven articles used randomization to fluid intake (clarified liquids/milk), solid food, or fasting in subgroups as the gold standard for assessing the accuracy of gastric ultrasound, and six of these studies were conducted in healthy volunteers [ 4 , 23 , 25 , 28 – 30 ], whereas the study by Arzola et al was conducted in women with late-term pregnancies [ 24 ]. Segura-Grau et al studied patients requiring upper gastrointestinal endoscopy, using endoscopic findings of gastric contents as the gold standard [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…Overall, a high risk of bias was identified in the majority of studies, and in terms of case selection, 2 articles had case controls in the study design and did not explicitly describe the inclusion of cases as consecutive or randomized, resulting in a high risk of bias (22%) [ 28 , 29 ]. Regarding the trials to be evaluated, three articles were at high risk (40%) [ 24 , 25 , 28 ], mainly because the threshold for diagnosing “high-risk stomach” was not given in these articles. There was an article that excluded patients with uncertain qualitative ultrasound evaluation and did not analyze all the included subjects, so there was a high risk in the case progress process [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have evaluated the utility of gastric POCUS in the context of anesthesia care, a majority of them have utilized designs where fasting volunteers drank a premeasured quantity of liquids with subsequent measurement of gastric antral CSA 8,10 . While the formula and the nomogram showed good correlation between estimated and measured volume in the first validation study of the technique, some studies have shown poor correlation of ultrasound measurements between observers 12,25 or between the estimated and measured gastric volume 11,14 and could be due to operator experience or the differences in the technique of delineating the cross‐sectional area. While we found a strong correlation between nomogram and formula‐based measurements, only a moderate degree of correlation was found between estimated volumes (nomogram or formula based) and measured volumes despite a majority of patients having low residual, and is an important finding of our study.…”
Section: Discussionmentioning
confidence: 99%